Exploring Internal Communication and Employee Relations Management for Effective Staff Performance in Nigeria Customs Service - Abdullahi Aliyu Maiwada (Britain International for Academic Research (BIAR-Publisher), 2024)
Exploring Internal Communication and Employee Relations Management for effective staff performance in the Nigeria Customs Service (NCS) is essential for understanding how internal practices can influence productivity, morale, and overall organizational efficiency. The objectives of the study are to evaluate the effectiveness of the current internal communication channels employed by the Nigeria Customs Service, to examine how internal communication influences improved employee performance in the Nigeria Customs Service, and to investigate the employee relations strategies employed by the Nigeria Customs Service to motivate and enhance job performance among its staff. The study adopted the Systems Theory, while the postulation of positivist approach of research design informed the choice of survey method. The positivist paradigm of research design believes in the quantitative method of data generation. The population of this study consist of the entire Officers and Men of the Nigeria Customs Service, which is about 15, 000. A sample size of 342 respondents was considered for the study. Stratified sampling was used to select the respondents while questionnaire was employed as a research instrument. The findings suggest that top-to-down communication channels established by senior management play a crucial role in conveying clear direction and expectations to employees within the NCS. This finding underscores the significant role of internal communication in shaping employees’ attitudes and behaviours towards their work responsibilities within the NCS. The study concludes that internal communication and employee relations management are fundamental to enhancing staff performance in the Nigeria Customs Service.